Influence of superplasticizers on mechanical properties and workability of cemented paste backfill. (15th January 2018) - Mangane, Mohamed Bini Coulibaly; Argane, Rabei; Trauchessec, Romain; Lecomte, André; Benzaazoua, Mostafa
Highlights: Superplasticizers pure molecules were used for their dispersant effect on CPB. Superplasticizers effects on CPB depend on theirs type and dosage. Superplasticizers' utilization allowed reducing binder content from 5 to 3%. Abstract: This paper presents new insights into the mechanical properties and workability of cemented paste backfills (CPBs) containing various superplasticizers. Effects of these admixtures on cement hydration were also evaluated. Five admixtures belonging to the main superplasticizer groups (lignosulfonate, naphthalene, melamine, and polycarboxylate) were used at 5, 7, and 10% by dry mass of binder (a mixture of 20% ordinary Portland cement (OPC) and 80% slag). The effects on CPBs formulated with OPC and the most effective superplasticizers were also studied. Results showed that superplasticizers influence on CPB performances depends on the type and dosage of the admixture. Polycarboxylate presented the best performances and allowed the achievement of the target consistency at lower water content (between 6 and 10%) without altering the mechanical strength of the CPBs. The results also reveal that a reduction in binder content (from 5 to 3%) could be achieved while still conserving CPB strength when using polycarboxylate admixtures.